Comparison of separation methods for immunomodulatory extracellular vesicles from helminths. Issue 5 (3rd May 2022) - Borup, Anne; Boysen, Anders T.; Ridolfi, Andrea; Brucale, Marco; Valle, Francesco; Paolini, Lucia; Bergese, Paolo; Nejsum, Peter
Abstract: Helminths survive within their host by secreting immunomodulatory compounds, which hold therapeutic potential for inflammatory conditions. Helminth‐derived extracellular vesicles (EVs) are one such component proposed to possess immunomodulatory activities. Due to the recent discovery of helminth EVs, standardised protocols for EV separation are lacking. Excretory/secretory products of the porcine helminth, Ascaris suum, were used to compare three EV separation methods: Size exclusion chromatography (SEC), ultracentrifugation (UC) and a combination of the two. Their performance was evaluated by EV yield, sample purity and the ability of EVs to suppress lipopolysaccharide (LPS)‐induced inflammation in vitro. We found that all three separation methods successfully separated helminth EVs with a similar EV yield. Functional studies showed that EVs from all three methods reduced LPS‐induced levels of tumour necrosis factor (TNF‐α) in a dose‐dependent manner. Overall, the three separation methods showed similar performance, however, the combination of UC+SEC presented with slightly higher purity than either method alone.